Physical exercise and social interaction in complex environments reverse memory deficits induced by inhalants. (August 2019) - Mercadillo, Roberto E; Mosco-Aquino, Ricardo; Páez-Martínez, Nayeli
Inhalant abuse is a global issue with major behavioral, cognitive, and social consequences. Some effects of this abuse are observed in memory deficits, but the organism–environment interactions are poorly understood. We propose that studying environmental enrichment (EE) in animal models allows the elucidation of adaptive behavior mechanisms to face harmful effects, as well as plausible translational interventions; however, the effects of the different elements that comprise the complexity of EE must be determined. In this work, we measured the effects of housing under five environments for 4 weeks on memory impairments induced by the repeated administration of toluene in mice (4000 ppm, 30 min/day for 4 weeks). Recognition memory was recovered after housing in a complete enriched environment involving voluntary exercise with running wheels, cognitive stimulation with objects to explore, and social interaction. However, enrichment with only voluntary exercise in social conditions produced a significant memory recovery. In addition, EE in isolation showed fewer beneficial effects, while cognitive stimulation, even under social conditions, did not reverse the memory impairment by itself. We argue that physical exercise and social interaction could derive in cognitive enhancement and be used to advise on psychosocial interventions.